2020
DOI: 10.3390/foods9101501
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositional Changes in Over-Oxidized Fish Oils

Abstract: A recent study has reported that the administration during gestation of a highly rancid hoki liver oil, obtained by oxidation through sustained exposure to oxygen gas and incident light for 30 days, causes newborn mortality in rats. This effect was attributed to lipid hydroperoxides formed in the omega-3 long-chain polyunsaturated fatty acid-rich oil, while other chemical changes in the damaged oil were overlooked. In the present study, the oxidation condition employed to damage the hoki liver oil was replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
2
8
0
1
Order By: Relevance
“…More specifically, after 120 d, the AV, POV, p-AV, and CDV were 7.62 ± 0.14 mg/g, 23.67 ± 0.55 meq/kg, 2.33 ± 0.03, and 33.57 ± 0.89, respectively. This observed increase in the AV is also consistent with previous studies [ 24 , 25 ] and is closely related to the free fatty acid content [ 26 , 27 ]. Previously, it was reported that the oxidation of fish meat during storage causes the breakage of ester bonds, which releases a large amount of free fatty acids and increases the AV [ 28 ].…”
Section: Results and Analysissupporting
confidence: 93%
“…More specifically, after 120 d, the AV, POV, p-AV, and CDV were 7.62 ± 0.14 mg/g, 23.67 ± 0.55 meq/kg, 2.33 ± 0.03, and 33.57 ± 0.89, respectively. This observed increase in the AV is also consistent with previous studies [ 24 , 25 ] and is closely related to the free fatty acid content [ 26 , 27 ]. Previously, it was reported that the oxidation of fish meat during storage causes the breakage of ester bonds, which releases a large amount of free fatty acids and increases the AV [ 28 ].…”
Section: Results and Analysissupporting
confidence: 93%
“…In another study, the incorporation of tea catechin (1 mM) or α-tocopherol (1 mM) in an oleic and linolenic acid–rich diacylglycerol oil, had no effect on the fatty acid composition of oil during a 10-day storage at 60 °C [ 52 ]. Similar to the results observed in this study for control and α-tocopherol-supplemented samples, Phung et al [ 53 ] reported an 8% decrease in EPA and DHA contents of hoki liver oil after 30 days of continuously bubbling the oil with oxygen gas and a 7% decrease when the oil was stored in an oven at 50 °C for 30 days.…”
Section: Resultssupporting
confidence: 89%
“…As OS is involved in many fields, e. g. environment, nutrition, disease, a wide variety of matrices are studied and analytical methods needs to be adapted. Thus, classical biological fluids (urine, [109][110][111] blood [99,112] ) or more specific ones (cerebrospinal fluid, [113,114] seminal fluid, secretome), animal tissues (muscle, kidney tissue, [115] brain tissue, [116] adipose tissue, [117] fibroblast cell line, spermatozoa, tumor biopsy) or plants or parts of plants (seaweed, oily extracts, oils, [118,119] seeds, [79] leaves, [120] etc.) will not follow the same sample preparation procedures (Figure 3).…”
Section: Analytical Workflowmentioning
confidence: 99%